Impaired mitochondrial function in chronically ischemic human heart - Stride, Nis; Larsen, Steen; Hey-Mogensen, Martin; Hansen, Christina N.; Prats, Clara; Steinbrüchel, Daniel; Køber, Lars; Dela, Flemming (American journal of physiology. Heart and circulatory physiology, 2013)
Chronic ischemic heart disease is associated with myocardial hypoperfusion. The resulting hypoxia potentially inflicts damage upon the mitochondria, leading to a compromised energetic state. Furthermore, ischemic damage may cause excessive production of reactive oxygen species (ROS), producing mitochondrial damage, hereby reinforcing a vicious circle. Ischemic preconditioning has been proven protective in acute ischemia, but the subject of chronic ischemic preconditioning has not been explored in humans. We hypothesized that mitochondrial respiratory capacity would be diminished in chronic ischemic regions of human myocardium but that these mitochondria would be more resistant to ex vivo ischemia and, second, that ROS generation would be higher in ischemic myocardium. The aim of this study was to test mitochondrial respiratory capacity during hyperoxia and hypoxia, to investigate ROS production, and finally to assess myocardial antioxidant levels. Mitochondrial respiration in biopsies from ischemic and nonischemic regions from the left ventricle of the same heart was compared in nine human subjects. Maximal oxidative phosphorylation capacity in fresh muscle fibers was lower in ischemic compared with nonischemic myocardium ( P < 0.05), but the degree of coupling (respiratory control ratio) did not differ ( P > 0.05). The presence of ex vivo hypoxia did not reveal any chronic ischemic preconditioning of the ischemic myocardial regions ( P > 0.05). ROS production was higher in ischemic myocardium ( P < 0.05), and the levels of antioxidant protein expression was lower. Diminished mitochondrial respiration capacity and excessive ROS production demonstrate an impaired mitochondrial function in ischemic human heart muscle. No chronic ischemic preconditioning effect was found.